Avaliação dos efeitos genéticos e ambientais na evolução do rendimento de grãos, qualidade de panificação e estabilidade de trigo - Bornhofen, Elesandro (2015)
Studies investigating historical cultivars of wheat are widely available and show significant annual gains in grain yield (GY) by many producing countries, while some report recent decrease in genetic progress. In this sense, the evaluation of the gains inherent to breeding programs appears as a measurement tool of efficiency and can help define future strategies. Thus, the first study of this dissertation aimed to measure the genetic progress for GY obtained in wheat breeding program of the Central Cooperative Agricultural Research (Coodetec) through the annual evaluation of lines on value of testing and use trials (VCU). We used data from 836 experiments, conducted in 40 locations in the 2004-2013 period. We used the REML/BLUP analysis to access the genotypic values, which were used to estimate the genetic progress by the similar method described by Vencovsky et al. (1986). The overall genetic progress of the breeding program was 61.59 kg ha-1 yr-1 (1.68% yr-1), however, was partially counterbalanced by negative environmental effects (-22.19 kg ha-1 yr-1; -0.58% year-1). The genetic progress by VCU region ranged from 31.38 kg ha-1 yr-1 (VCU 4) and 115.33 kg ha-1 yr-1 (VCU 1). In commercial cultivars released between 1998 and 2014, we obtained genetic progress equal to 1% yr-1. The second study aimed to evaluate the same breeding program, but for wheat industrial quality traits. We used data from two cities of Paraná state (Cascavel and Palotina). The historical series consisted of eight years (2005 to 2012) and 458 genotypes, including lines and cultivars. The following characters were used in the study: gluten strength (W), tenacity (P), extensibility (L) and falling number (FN). We found tendency of disequilibrium in P/L ratio, due to the genetic gain in P be positive (2.11% yr-1) and L be negative (-0.93% yr-1). The genetic progress was 1.30% yr-1 in W, reflecting the efforts of the breeding program to increase the wheat industrial quality. The third study aimed to compare methods of evaluation of the stability and adaptability in wheat, in order to identifying essential methodologies. We used GY data from 22 wheat genotypes evaluated in three locations (Guarapuava, Cascavel and Abelardo Luz) for two growing seasons (2012 and 2013), totaling six environments. The experimental design used in each experiment was a randomized complete block design with three replications. In the evaluation of genotype vs. environment interaction (GEI), methodologies were used based on mixed models, analysis of variance, linear regression, multivariate and non-parametric analysis. To selecting stable genotypes with high GY is indicated using the method of the harmonic mean of the relative performance of genetic values (MHPRVG) based on mixed models in association with the graphical analysis GGE biplot, due to the ability to infer about environments, genotypes and their relationships.